COMPARISON OF IATROGENIC PROXIMAL SURFACE DAMAGE DURING ABUTMENT PREPARATION BY DIFFERENT GROUPS OF PRACTITIONERS - Mohammad Sartaj Khan; Nuzhat Ayub; Muhammad Raza; Ata Elahi; Fahimullah Khattak; Hussain Naif AlSharif (Pakistan Oral & Dental Journal, 2021)
To find out and compare the iatrogenic damage of proximal surfaces adjacent to tooth preparation by different groups of practitioners. 120 casts from different laboratories of Peshawar were examined under naked eye and magnifying glass by two different examiners from September 2017 to October 2018. Casts having one tooth anteriorly or posteriorly, undamaged, prepared for fixed partial dentures or crowns and cases with complete laboratory request form were included in the study. Data was recorded on pre-structured Proforma and was analyzed by using SPSS (version 22). Out of 71% damage of proximal surfaces, 39% was visible by magnifying glass and 11% by naked eye. Highest degree, type and extent of damage was recorded for house officers. There was a significant difference regarding study parameters between all the different groups of practitioners (p=0.000). Maximum damage during preparation is done by House officers due to lack of their experiences.